Africa’s food policy needs sharper teeth - Masimba Tafirenyika (Africa Renewal, 2014)
Amid raving economic forecasts that Africa will be the next big emerging market, chronic food shortages remain stubbornly immune to solutions. The African Union is aware of this weak link and is working to convince its members to boost investments in agriculture. To emphasize the central role of agriculture in Africa’s economic growth, the regional body has declared 2014 as the Year of Agriculture and Food Security.